29. TREATMENT OUTCOMES OF FLEXIBLE URETEROSCOPY WITH HOLMIUM LASER FOR RENAL CALCULI AT TRANSPORT HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the clinical characteristics, paraclinical findings, and treatment outcomes of renal calculi managed with flexible ureteroscopy and holmium laser lithotripsy at Transport Hospital.Methods: A cross-sectional study was conducted on 125 patients diagnosed with renal calculi and treated with flexible ureteroscopy and holmium laser lithotripsy at Transport Hospital from January 2023 to December 2024. Patient characteristics including age, gender, occupation, stone location, stone number, and stone size were collected. Stone-free rates at 1 week and 1 month were assessed. Risk factors were compared between patients with a single stone and those with multiple stones (≥2).Results: The mean age of patients was 52.3 ± 11.7 years; males accounted for 58.4%. The most common stone location was the renal pelvis (42.4%), followed by upper calyces (23.2%) and lower calyces (21.6%). Patients with multiple stones represented 34.4%, significantly associated with age ≥60 years (p
Keywords: Renal calculi; Flexible ureteroscopy; Holmium laser lithotripsy; Stone-free rate